Jedajův příspěvek k teorii minima naturalia v kontextu středověkého židovského averroismu - Hana Budíková (Reflexe)
In his epitome of Aristotle’s Physics, Averroes discusses the problem of the First-moved part. According to his opinion, the First-moved part is a perceptible body, which nevertheless itself consists of imperceptible and immovable parts. Yeda’yah considers Averroes’ statement to be false and offers a more logical solution in his commentary to Averroes’ epitome. He looks at the problem of a perceptible body from two different perspectives. The most important idea of his solution is that he introduces a conceptual distinction between guf and geshem, which are synonyms, meaning “body” in the standard Hebrew philosophical terminology. In his new terminology, guf is an indivisible body capable of being moved, whereas geshem is a divisible body incapable of being moved on its own, except as part of the former. The First-moved part is then a minimal indivisible movable part of a body, which is called guf, i.e. body unit, and consists of several smaller divisible unmovable parts, which are understood as geshem, i.e. corporeal substance.